2020
DOI: 10.21660/2020.69.29669
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between the Plasticity Index and Key Consolidation Parameters of Soft Ground Stabilized by Vacuum Preloading Together With Vertical Drains

Abstract: This study addressed the relationship between the plasticity index (PI) and the key parameters of the vacuum consolidation process including the consolidation time (t), the degree of consolidation (U), and the thickness of the treated soft soil layer (H) when improving soft ground by vacuum preloading together with vertical drains. For this purpose, the coupled analysis technique which combines SEEP/W and SIGMA/W modules in Geostudio commercial software is applied for the simulation. Three different foundation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Pham Quang Dong [19] discussed the relationship between the plasticity index and consolidation parameters from the vacuum process such as the total degree of consolidation of soil (Ut), time of consolidation (t), and thickness of the treated soft soil layer (H). The results showed that there is a linear relationship between consolidation time and plasticity index, the higher the IP the longer the soil to undergo the consolidation process.…”
Section: Introductionmentioning
confidence: 99%
“…Pham Quang Dong [19] discussed the relationship between the plasticity index and consolidation parameters from the vacuum process such as the total degree of consolidation of soil (Ut), time of consolidation (t), and thickness of the treated soft soil layer (H). The results showed that there is a linear relationship between consolidation time and plasticity index, the higher the IP the longer the soil to undergo the consolidation process.…”
Section: Introductionmentioning
confidence: 99%
“…Managing uncontrolled seepage through the body and foundation of embankments is a major concern for engineers operating dams [9]. The seepage flow within hydraulic structures, like dams, has a significant impact on their stability and deformation [10][11][12]. Seepage might trigger slope failure by generating high pressure on the pores within the soil or by increasing the wetness of the slope.…”
Section: Introductionmentioning
confidence: 99%